Effect of Waiting Room Facilities on Passenger Comfort at Mopah Merauke Airport - Wahyu Dian Rositasari; Ika Fathin Resti Martanti (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Mopah Merauke Airport is one of the airports serving flights in Merauke, South Papua. The purpose of this study is to find out whether waiting room facilities affect passenger comfort, and how much waiting room facilities affect passenger comfort at Mopah Merauke Airport. This research uses quantitative methods. The research was conducted at Mopah Merauke Airport from 1 to 31 December 2022 where passengers at Mopah Merauke Airport were the objects of this study. The source of the data used in this study was obtained from the results of distributing questionnaires to passenger respondents at Mopah Merauke Airport. The results of the study concluded that the waiting room facilities had a significant effect on passenger comfort of 68.6%.